2012
DOI: 10.1136/bmjopen-2011-000638
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-experimental evaluation of an HIV prevention programme by peer education in the Anglican Church of the Western Cape, South Africa

Abstract: IntroductionReligion is important in most African communities, but faith-based HIV prevention programmes are infrequent and very rarely evaluated.ObjectiveThe aim of this study was to evaluate the effectiveness of a church-based peer education HIV prevention programme that focused on youth.DesignA quasi-experimental study design compared non-randomly chosen intervention and control groups.SettingThis study was conducted in the Cape Town Diocese of the Anglican Church of Southern Africa.ParticipantsThe interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…Thus, it may be argued that Vhutshilo increased young people's sense of agency. These findings are in keeping with those recorded with regard to MCPs (Mash & Mash 2012), changes in HIV attitudes and knowledge (Ott et al 2003), and young people's proclivity to engage more actively in discussion after peer-led sessions (Rickert et al 1991).…”
Section: Knowledge Attitude and Behaviour Changesupporting
confidence: 69%
See 3 more Smart Citations
“…Thus, it may be argued that Vhutshilo increased young people's sense of agency. These findings are in keeping with those recorded with regard to MCPs (Mash & Mash 2012), changes in HIV attitudes and knowledge (Ott et al 2003), and young people's proclivity to engage more actively in discussion after peer-led sessions (Rickert et al 1991).…”
Section: Knowledge Attitude and Behaviour Changesupporting
confidence: 69%
“…Third, the unavailability of existing survey questions to measure the impact of peer education and its role in behaviour change, and the lack of resources required to design new questions, was a final limitation. Mash and Mash (2012) have also noted the need for more effective peer education evaluations. However, research will always be constrained by available resources.…”
Section: Methodological Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV peer education has been found to be effective in improving adolescent's HIV/AIDS knowledge, intentions regarding condom use, self-efficacy to refuse sex, and delay in sexual behaviors (Caron et al, 2004;Mash & Mash, 2014). One study reported contradictory findings concluding that a peer education program was not effective in reducing the age of sexual debut or condom use (Mason-Jones, Mathews, & Flisher, 2011).…”
Section: Literature Reviewmentioning
confidence: 92%